Cover Picture: Reactions of Group 4 Metallocene Complexes with Mono‐ and Diphenylacetonitrile: Formation of Unusual Four‐ and Six‐Membered Metallacycles (Chem. Eur. J. 13/2013). Issue 13 (15th March 2013) - Becker, Lisanne; Burlakov, Vladimir V.; Arndt, Perdita; Spannenberg, Anke; Baumann, Wolfgang; Jiao, Haijun; Rosenthal, Uwe
<x xml:space="preserve">Abstract</x> The route taken depends on the metals and Cp′ ligands chosen, as illustrated by reactions of Group 4 metallocene complexes and diphenylated acetonitrile, Ph2CHCN, which undergo coupling, coordination, or H‐shifts. Additionally, for zirconocene, an unexpected six‐membered fused zirconaheterocycle was formed by changing the substrates to monophenylated acetonitrile, PhCH2CN, and bis(trimethylsilyl)butadiyne. More details of this fascinating chemistry are reported in the Full Paper by U. Rosenthal and co‐workers on page 4230 ff. The background of the cover shows different destinations in Rostock and Warnemünde.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>